Immune Landscape of CMV Infection in Cancer Patients: From “Canonical” Diseases Toward Virus-Elicited Oncomodulation - El Baba, Ranim; Herbein, Georges (Frontiers in Immunology, 2021)
Human Cytomegalovirus (HCMV) is a highly prevalent herpesvirus, persistently infecting high percentages of the world population. Despite the robust host immune responses, HCMV is capable of replicating, evading host defenses, and establishing latency throughout life by employing multiple immune-modulatory strategies. HCMV has co-evolved with the hosts, mounting various strategies to evade immune effector cells and successfully win the HCMV-immune system battle mainly through maintaining its viral genome, impairing HLA Class I and II molecule expression, evading from natural killer (NK) cell-mediated cytotoxicity, interfering with cellular signaling, inhibiting apoptosis, escaping complement attack, and stimulating immunosuppressive cytokines (immune tolerance). HCMV expresses several gene products that modulate the host immune response and promote alterations in regulatory proteins and non-coding RNA. These changes are associated with several complications, such as immunosenescence and malignant phenotypes leading to immunosuppressive tumor microenvironment (TME) and oncomodulation. Hence, tumor survival is promoted by affecting cellular proliferation and survival, invasion, immune evasion, immunosuppression, and giving rise to angiogenic factors. Viewing HCMV-induced evasion mechanisms will contribute to the development of novel adapted therapeutic approaches against the virus, especially since immunotherapy has revolutionized cancer therapeutic strategies. Since tumors acquire immune evasion strategies, anti-tumor immune responses can be prominently triggered by multimodal strategies aiming on one side to induce immunogenic tumor cell death and on the other side to actively counteract the immune suppressive microenvironment.